2014
DOI: 10.25289/ml.2014.3.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Flat Warts (Verrucae Planae) on the Q-Switched Laser-Assisted Tattoo Removal Site

Abstract: Flat warts, or verrucae planae, are a common cutaneous infection, which tends to be multiple and grouped. They are more often found on sunexposed areas such as the face, neck, and extremities, and sometimes develop at the sites of skin trauma. The author reports on a case of flat warts which developed on the Q-switched laser tattoo removal site. Histologic findings confirmed the diagnosis of verruca plana. The author suggests that activation of the human papillomavirus should be included in the possible compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The warts appeared two weeks after an acute sunburn involving tattooed and normal skin, but the warts were confined to the tattooed area, suggesting that the virus was probably inoculated at the time of tattooing and remained latent, and the UV light acted as a trigger inducing its activation [ 68 ]. Rho et al highlighted the onset of flat warts on the Q-switched laser-assisted tattoo removal site in a 23-year-old patient, 3 weeks after the procedure [ 111 ]. The authors suggested that HPV was probably latent within tattooed skin, and that the treatment caused the alteration of the epidermal barrier that allowed the virus to spread.…”
Section: Potential Mechanisms Involved In the Occurrence Of Viral Inf...mentioning
confidence: 99%
“…The warts appeared two weeks after an acute sunburn involving tattooed and normal skin, but the warts were confined to the tattooed area, suggesting that the virus was probably inoculated at the time of tattooing and remained latent, and the UV light acted as a trigger inducing its activation [ 68 ]. Rho et al highlighted the onset of flat warts on the Q-switched laser-assisted tattoo removal site in a 23-year-old patient, 3 weeks after the procedure [ 111 ]. The authors suggested that HPV was probably latent within tattooed skin, and that the treatment caused the alteration of the epidermal barrier that allowed the virus to spread.…”
Section: Potential Mechanisms Involved In the Occurrence Of Viral Inf...mentioning
confidence: 99%